PERBANDINGAN KEANEKARAGAMAN DAN PREDOMINANSI FAUNA TANAH DALAM PROSES PENGOMPOSAN SAMPAH ORGANIK - Fitrahtunnisa, Fitrahtunnisa (Bumi Lestari; Vol 13 No 2 (2013), 2012)
Abstract Actually, the problem of garbage can be solved by a good management, for example decomposition. Decomposition occure as a result of soil fauna activities. This research was aimed to analyse comparation the diversity and predominance of soil fauna in the decomposition all kinds of organic garbage. It was designed as an experimental study with garbage variation were : the agriculture garbage, the cattle faeces, the city garbage, mixture of agriculture garbage and faeces of cattle, mixture of agriculture and city garbages, mixture of cattle faeces and city garbage, and mixture of three kinds of garbage. The soil faunas were collected with Pitfall-traps and soil cores. The diversity indeks (H’) of soil fauna was analized by Shannon-Wienner indeks, while the predominance of soil fauna was counted based on the base of its relative abundance (RA). The highest diversity indeks of soil fauna was found at PTK, H’=3,01, while the lowest was found at P, H’=1,60. The kinds of predominant soil fauna were Hypogastrura armata (RA=71%), Carohodes marginatus (RA=54%), Cllohmannia gigatea (RA=30,3%), Phidole sithyesi (RA=19,1%), Suctobelba obtusa (RA=13,9%), Polyrhachis hauxwelli (RA=9,27), Lepidocyrtus pictus (RA=8,85%), Tetranychus canadensis (RA=7,07%), Narceus americanus (RA=7%), Entomobrya cingula (RA=6,82%), Lasius fuliginosus (RA=5,14%), and Isotomurus tricolor (RA=5,03%).
Keywords: Key words : diversity, decomposition, soil_fauna